Convulsiones del lóbulo Occipital, en pacientes con Hiperglicemia no cetósica - Rodríguez Ascón, Larry José Luis (2019)
In recent years, the incidence of diabetes mellitus in the world population has been increasing, as well as in our country, being one of the main diseases, which has great implications for the quality of life of those who suffer from it, due to its great repercussions clinics product of acute and chronic complications. Because hyperglycemia is primarily responsible for these complications; Therapies are aimed at the control of Hyperglycemia, however, despite this, and mainly due to poor adherence to treatment, many of the patients present with ketosic and non-ketosic hyperglycemia crisis (HNK), which could become recurring Non-ketosic hyperglycemia is defined as that clinical syndrome comprised of hyperglycemia, serum hyperosmolarity and intracellular dehydration, with low levels or in the absence of ketoacidosis (1). Polydipsia, polyuria, and weight loss, are the most common constitutional symptoms. In many patients with HNK the state of consciousness is not severely altered, particularly if the patient remains well hydrated.